PEMANFAATAN TEPUNG BERAS MERAH DAN BERAS HITAM DALAM PEMBUATAN PRODUK EDIBLE SPOON - Laurensia Maria Yulian Dwiputranti Darmoatmodjo; Erni Setijawaty; Joliska Wongsowinoto; Brenda Brenda; Florence Ancilla (Journal of Food Technology and Agroindustry, 2023)
The most widely used tableware is plastic spoon. However, its usage can cause environmental problems in the form of plastic waste. This plastic waste can be overcome by alternative innovations of making environmentally friendly tablespoon or edible spoon. Edible spoon can be made from a mixture of cereal flour, namely wheat flour, red rice flour, and black rice flour. Gluten from wheat flour is used to form a sturdy edible spoon texture, while red rice flour and black rice have anthocyanin pigments that act as natural dyes and antioxidants. The type of cereal flour used affects the characteristics of the edible spoons produced. The purpose of this study was to determine the physical characteristics and antioxidant activity of edible spoons made from a mixture of flour and red rice flour as well as wheat and black rice flour. This experiment used a randomized block research design (RBD) with 6 levels of treatment comparing the use of wheat flour with red rice flour or black rice flour, namely 65:35; 60:40; 55:45; 50:50; 45:55; and 40:60. The research data was analyzed by ANOVA and DMRT (α=5%). The fracture power of black and red rice edible spoons ranged from 13,196±0,5312 to 71,545±0,0091 and 15,637±0,0113 to 37,348±0,0230, the rehydration power range of black and red rice edible spoons were 16,56±0,7332 to 25,75±0,0005 and 14,88±0,1357 to 17,81±1,3077, as well as the antioxidant activity for red rice edible spoons were 87,6250 to 97,5500 and black rice 85,1250 to 98,0250.